The Diversity of Wood Vegetations along the stream of Hot Water Spring of Momiwaren Protected Forest in South Manokwari - Rusdy Angrianto, Rima Herlina S. Siburian, Dan Wachid Raharjo (International Journal of Advanced Science and Technology, 2020)
The Momiwaren protected forest area is one of the areas in South Manokwari Regency that has hot springs. This area is not in the volcano area. However, the resulting hot springs cause sulfur aromas surrounding the area. This area is a protected forest overgrown by various species of trees. For this reason, it is necessary to determine the structure and composition of plants in this area due to the presence of hot springs in this location. This research was carried out in the South Manokwari, Momiwaren Village. The results showed that the number of vegetation types in the area along the hot water stream was as many as 106 types which were divided into several levels: Seedling phase consisting of 35 species with 88 individuals and was dominated by Vatica rassak with important value index (IVI) of 35,770%; sapling phase consists of 55 species with 129 individuals and was dominated by Vatica rassak with IVI of 27.506%, Pole phase consists of 29 species with 45 individuals and was dominated by Vatica rassak with IVI of 28,069%, and tree phase consists of 22 types with individual numbers 56 and was dominated by Vatica rassak with IVI of 59,803%. The results of this study indicated that the spread of Vatica rassak exists at all levels of plants and was a dominant species along the stream of hot water spring.